The effect of lighting on the circadian rhythm and its applications in a healthcare environment - Gutknecht, Michelle (Kansas State University, 2014)
The correlation between natural and artificial lighting and the human circadian rhythm was researched to determine how changing artificial lighting design could improve the working environment in healthcare facilities. Research showed that human circadian rhythm is largely influenced by daylight and the accompanying light color (CCT) change in a day. Consequently, healthcare providers who are not exposed to daylight are isolated from this natural indicator. This can disjoint their circadian cycles from a normal rhythm and lead to physiological and psychological complications. Daylighting and standard artificial lighting design conditions were observed at Mercy Regional Medical Center (MRMC) in Manhattan, Kansas,. Then, healthcare providers at MRMC were anonymously surveyed about their perceived alertness throughout a typical working shift . The data was charted and plotted against a normal circadian rhythm to demonstrate whether a normal or disjointed cycle was experienced by healthcare providers. The comparison of this data to observed lighting conditions exhibited the necessary influence of daylight on achieving a normal circadian rhythm. This study reinforced the information available from many other sources connecting healthcare lighting and the circadian rhythm. Working on this premise, research suggested two lighting designs that would improve the working environment in healthcare facilities. The first of these would be the inclusion of circadian rooms. Special rooms in a healthcare facility would be available to staff in order to provide light therapy. Short wavelength blue light, experienced at optimal times throughout a shift, would act as stimulants (similar to daylight cues), adjusting employees' circadian cycles to normal when daylight exposure was unattainable. Alternately, a healthcare facility working on set, not-staggered, shifts could incorporate a variable lighting system. This system would rely on specialized lights to alter light color (CCT) throughout a shift to mimic daylight rhythms. Accordingly, staff would be exposed to daylighting cues from artificial sources and experience normal circadian rhythms.
Keywords: Circadian rhythm; Lighting; Healthcare; Architectural engineering (0462)